2001
DOI: 10.1002/ajmg.10002
|View full text |Cite
|
Sign up to set email alerts
|

Frog decline, frog malformations, and a comparison of frog and human health

Abstract: The decline in frog populations and the increase in the frequency of frog malformations are discussed. Topics considered for analysis include chytridiomycosis, retinoids, UV-B radiation, chemical contaminants, environmental threats, introduced invasive species and predation, unsustainable use, and enigmatic decline. Care must be taken to distinguish between hypotheses, laboratory experiments, and the findings in feral frog populations. Clearly, the causes of population decline and malformations are heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
1
30
0
Order By: Relevance
“…global warming and diseases, the major cause appears to be chemical pollution owing to the increased contamination of natural water bodies by agrochemicals (Green, 1999;Cohen 2001;Daniels, 2003;Hayes et al, 2006;Wake, 2007). Field studies have indicated that there is a correlation between the use of chemical pesticides and emergence of the amphibian larvae with developmental deformities in Northern America (Glare and O'Callaghan, 1999).…”
Section: Amputation Of Tail and Treatmentmentioning
confidence: 96%
See 1 more Smart Citation
“…global warming and diseases, the major cause appears to be chemical pollution owing to the increased contamination of natural water bodies by agrochemicals (Green, 1999;Cohen 2001;Daniels, 2003;Hayes et al, 2006;Wake, 2007). Field studies have indicated that there is a correlation between the use of chemical pesticides and emergence of the amphibian larvae with developmental deformities in Northern America (Glare and O'Callaghan, 1999).…”
Section: Amputation Of Tail and Treatmentmentioning
confidence: 96%
“…In recent years, owing to water pollution, there has been an increase in the production of amphibian fauna with gross malformations aff ecting survival ability, leading to overall decline in populations (Wake, 1991;Hayes et al, 2003). These have prompted serious concern regarding the biological status of many anuran species (Green, 1999;Cohen, 2001;Daniels, 2003;Hayes et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…These causes may occur synergistically (Kiesecker, 2002) and may relate to recent human-induced environmental damage (Blaustein and Johnson, 2003;Lannoo, 2008). The rate of malformed frogs in nature seems to have increased in recent years (Cohen Jr., 2001;Blaustein and Johnson, 2003;Schoff et al, 2003;Lannoo, 2008) and malformed frogs may indicate degraded environmental health (Ouellet et al, 1997;Roy, 2002).…”
mentioning
confidence: 96%
“…If the survival of Pleurogenoides is strongly associated to water frogs as the key host within the life-cycle, Pleurogenoides might soon become a vanishing genus at least in Europe because of the current widespread frog population decline [16]. In that case the absence of Pleurogenoides larval stages in the snails will open free ecological niches -chances to use these snails as hosts -for other fl ukes.…”
Section: Discussionmentioning
confidence: 99%